MICROTEACHING HOLISTIK DALAM MENYIAPKAN PROFESIONALISME CALON GURU PAI: SYSTEMATIC LITERATURE REVIEW - Fajarudin; Muhammad Akmansyah; Zahra Rahmatika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of Microteaching practice in preparing professional prospective Islamic Religious Education (PAI) teachers and to identify critical gaps regarding the spiritual and reflective dimensions in the existing literature. The study was conducted using the Systematic Literature Review (SLR) method, guided by the PRISMA 2020 framework. Following a rigorous staged selection process, a qualitative synthesis was performed on 10 final articles derived from 202 initially identified records. The findings indicate that Microteaching is highly effective in developing technical skills and mastering Pedagogical Content Knowledge (PCK), but its evaluation tends to be mechanistic and fails to capture the Holistic dimension, specifically the spiritual and ethical aspects vital for PAI teacher professionalism. The main contribution (novelty) of this study is the proposed framework for the Holistic PAI Microteaching Model. This model suggests a paradigm shift toward reflective-clinical teacher education, adapting reflection into the mechanism of muhasabah (spiritual self-reflection), supported by technology integration such as video-supported collaborative learning to train ethical response and character. It is concluded that the adoption of the Holistic PAI Microteaching Model is a methodological imperative to produce graduates who are not only technically proficient but also possess complete character integrity and spirituality.